2018
DOI: 10.1002/jlcr.3610
|View full text |Cite
|
Sign up to set email alerts
|

Ra‐224 labeling of calcium carbonate microparticles for internal α‐therapy: Preparation, stability, and biodistribution in mice

Abstract: Internal therapy with α‐emitters should be well suited for micrometastatic disease. Radium‐224 emits multiple α‐particles through its decay and has a convenient 3.6 days of half‐life. Despite its attractive properties, the use of 224Ra has been limited to bone‐seeking applications because it cannot be stably bound to a targeting molecule. Alternative delivery systems for 224Ra are therefore of considerable interest. In this study, calcium carbonate microparticles are proposed as carriers for 224Ra, designed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 58 publications
2
62
0
Order By: Relevance
“…Residue from the CaCO 3 microparticles was observed at necropsy up to day 7 in the previously reported biodistribution studies [24] but was not seen in the therapy studies performed here when the mice were sacrificed between 26 and 70 days after administration. Even though particle residue was seen at the early time points, they did not cause adhesions, and the lack of a permanent implant or other signs of remaining residue after day 26 suggests that the CaCO 3 microparticles are well tolerated and supports the general notion of CaCO 3 being a biocompatible and biodegradable material.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Residue from the CaCO 3 microparticles was observed at necropsy up to day 7 in the previously reported biodistribution studies [24] but was not seen in the therapy studies performed here when the mice were sacrificed between 26 and 70 days after administration. Even though particle residue was seen at the early time points, they did not cause adhesions, and the lack of a permanent implant or other signs of remaining residue after day 26 suggests that the CaCO 3 microparticles are well tolerated and supports the general notion of CaCO 3 being a biocompatible and biodegradable material.…”
Section: Discussionmentioning
confidence: 48%
“…The preparation of 224 Ra-labeled CaCO 3 microparticles has been described in detail elsewhere [24] . In brief, CaCO 3 microparticles were prepared by a spontaneous precipitation method which yielded particles with individual diameters ranging from 3 to 15 μm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous attempts to bind 223 Ra within liposomes have not been successful because of their low stability in physiological fluids and relatively large diameter [ 28 , 29 ]. However, the next studies have shown better immobilization of 223 Ra in magnetite nanoparticles [ 30 ], hydroxyapatites [ 31 ], barium sulfate nanoparticles [ 32 ], and CaCO 3 microparticles [ 33 ]. In addition, the procedure of incorporation of 223 Ra in NaA nanozeolites was developed by our group [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%